EFL Consonant Pronunciation: A PRAAT & CALD-based Study of Indonesian Learners - Muhammad Isnur Alkarni Akis; Jamilah Jamilah (English Department FBS UNP, 2025)
This study examines the pronunciation difficulties encountered by English as a Foreign Language (EFL) students while articulating specific English consonant sounds absent in Indonesian phonology. It also examines the elements that contribute to these pronunciation issues. The research investigates six English consonants: /v/, /θ/, /ð/, /ʒ/, /j/, and /w/. A mixed-method approach was utilized, collecting qualitative data via interviews and thorough pronunciation analysis, while quantitative data were obtained through a perception questionnaire. Thirty ninth-grade students’ from Mts Muhammadiyah Karangkajen Yogyakarta, Indonesia, participated in the study. Pronunciation accuracy was assessed using PRAAT and audio samples from the Cambridge Advanced Learner’s Dictionary (CALD). The findings reveal that /ð/ is the most challenging sound, as appropriately said by just 42% of students, while /v/ is the least difficult, with 51% accuracy. The pronunciation challenges revealed significant differences in pitch and intensity between students’ pronunciations and reference sounds. Furthermore, students reported inadequate feedback regarding their pronunciation and perceived English classes as uninteresting. The study underscores the importance of comprehensive educational methods that include all English consonant and vowel sounds to enhance pronunciation instruction.